Manajemen Pelayanan Administrasi Terpadu (PATEN) Berdasarkan Perwal Kota Cilegon Nomor 35 Tahun 2014 Pada Kecamatan Grogol dan Kecamatan Purwakarta - Saepudin, Eli Apud (ANTASENA: Governance and Innovation Journal, 2024)
Public services are all activities in the context of fulfilling basic needs in accordance with the basic rights of every citizen and resident of a service good and or administrative services provided by service providers related to public interests. Services are provided to fulfill community rights, both civil services and public services regulated in laws and regulations. Within this scope, including education, teaching, work and business, housing, communication and information, environment, health, social security, energy, banking, transportation, natural resources, tourism, and other strategic sectors. The method used in this research is descriptive qualitative data obtained by direct observation and direct interviews at the intended location, the purpose of conducting this research seeks to improve the quality of life and life for the greatest welfare of the village community. In improving the welfare of rural communities and the quality of human life and poverty reduction through the fulfillment of basic needs, development of facilities and infrastructure, development of local economic potential, and sustainable use of natural resources and the environment.